DTC hybrid by different techniques of observation with Artificial Neuronal Network (ANN) for induction machine drives - Dris Ahmed; Mokhtar Bendjebbar; Aek Belaidi (Institute of Advanced Engineering and Science, 2019)
In this article, we present the construction of observers of rotor flux and mechanical speed needed for robust control of the induction machine. Two observers will be developed for comparison. The first is based on the techniques MRAS and the second is observer of KUBOTA, with the enhanced DTC-ANN (by artificial intelligence),